Synthesis and evaluation of vinyl sulfones as caspase-3 inhibitors. A structure-activity study - Newton, Ana S. (2011)
The first structure–activity relationship study of vinyl sulfones as caspase-3 inhibitors is reported. A series of 12 vinyl sulfones was synthesized and evaluated for two downstream caspases (caspases-3 and -7). Dipeptidyl derivatives were significantly superior to their counterparts containing only Asp at P1, as caspase-3 inhibitors. Fmoc-Val-Asp-trans-CH CH–SO2Me was the most potent inhibitor of caspase-3 in the series, with a IC50 of 29 μM and a second-order rate constant of inactivation, kinact/Ki, of 1.5 M−1 s−1. Computational studies suggest that the second amino acid occupies position S3 of the enzyme. In addition, Fmoc-Val-Asp-trans-CH CH–SO2Ph was inactive for caspase-7 for the tested concentrations.